CLINICOMICROBIOLOGICAL STUDY OF INFECTIONS CAUSED BY ACINETOBACTER SPECIES - Shridhar, Sridevi; Bhat, Sevitha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: To study the rate of isolation of Acinetobacter species, its antibiogram and associated risk factors. Methods: Retrospective time bound study for 6 months. The study included 191 consecutive clinical significant isolates of Acinetobacter species isolated from various specimens. The identification and antibiotic susceptibility testing by modified Kirby Bauer and Vitek Compact system 2. Results: Maximum isolation of Acinetobacter species was from suction tip (31.94%), sputum (19.89%), urine (14.66%), blood (10.47%), and others. The species was most sensitive to colistin (97.87%) and polymyxin B (99.43%). The species was most resistant to imipenem (72.62%) and gentamicin (66.66%). The common risk factors were invasive procedure, duration of intensive care unit stay, and malignancies. Conclusion: Acinetobacter has emerged as a major nosocomial pathogen. Antibiotic resistance is on rise. Proper antibiotic stewardship is required to curtail antibiotic resistance in this region. Keywords: Acinetobacter spp., Antibiotic resistance, Health care associated pathogen Â